Testing Frankel's Monetary Model in Algeria Evidence from 1995 to 2023 (مجلة إضافات إقتصادية, 2025)
This study analyzes short- and long-term determinants of exchange rate movements using the ARDL model. Based on monetary and output theories, it considers money supply, income differentials, and interest rate spreads. Results confirm a stable long-run cointegration: domestic money growth depreciates the currency, while higher income strengthens it. Interest rate differentials affect short-term fluctuations but not the long run. The error correction term shows rapid adjustment to equilibrium. Short-term dynamics also capture lagged effects of money and income. Findings support uncovered interest parity. Diagnostic tests validate model stability, stressing the importance of prudent monetary policy and balanced growth for exchange rate stability.Jel Classification Codes: F31, E52, E41, C32.